2009
DOI: 10.1097/wnr.0b013e32831befc1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in auditory processing in peripersonal space: an event-related potential study

Abstract: Further processing of auditory stimuli in free-field is attenuated when participants are in contact with speakers versus not touching them. Studies in the visual domain have found that men and women utilize different strategies for processing spatial information. In the current study, we examined sex-related differences in event-related potentials (ERPs) while men and women performed an auditory discrimination task in peri-personal space when either holding speakers or resting their hands in their laps. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…The higher male performance in this task may parallel findings of men outperforming women in right-monaural vertical sound localization, auditory motion perception of looming sounds, and auditory spatial attention (Lewald, 2004;Neuhoff et al, 2009;Simon-Dack et al, 2009), as well as men outperforming women in visuospatial attention (e.g., Kimura, 1992;Stoet, 2010; for a detailed discussion, see Zündorf et al, 2011). These sex-related differences in spatial attention and the effect of sex demonstrated here are possibly of similar origin.…”
Section: Sex Differencessupporting
confidence: 69%
See 1 more Smart Citation
“…The higher male performance in this task may parallel findings of men outperforming women in right-monaural vertical sound localization, auditory motion perception of looming sounds, and auditory spatial attention (Lewald, 2004;Neuhoff et al, 2009;Simon-Dack et al, 2009), as well as men outperforming women in visuospatial attention (e.g., Kimura, 1992;Stoet, 2010; for a detailed discussion, see Zündorf et al, 2011). These sex-related differences in spatial attention and the effect of sex demonstrated here are possibly of similar origin.…”
Section: Sex Differencessupporting
confidence: 69%
“…The visual spatial attention of women appeared to be more susceptible to influences by irrelevant events than that of men (e.g., Stoet, 2010). Electrophysiological and neuroimaging findings from both the visual and the auditory modalities indicated that different neural networks were recruited in the two sexes to perform spatial tasks, which has been discussed in terms of a simplified model of male bottom-up and female top-down strategies in spatial processing (e.g., Hugdahl et al, 2006;Simon-Dack et al, 2009). …”
Section: Introductionmentioning
confidence: 95%
“…A second explanation may be related to the fact that the frequency discrimination task utilized in this study is based on temporal processing abilities that are known to be superior in males [13]. It has been suggested that the ability to discriminate between two successive puretones is dependent on two processes, temporal and spectral [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some showed young adult males to have greater sensitivity in several auditory tasks, including (1) discrimination of small differences in interaural arrival time and intensity [11], (2) temporal order judgment [12], (3) temporal processing as measured by discrimination of amplitude envelope onset rise times [13], (4) detection of a pure-tone in simultaneous masking with random frequency maskers [3], (5) sound localization [14], (6) spatial attention [5], and (7) discrimination of small differences in pitch and loudness [4]. Other data showed young adult females to have better hearing sensitivity by 1-4 dB, particularly for frequencies > 2 kHz (e.g., [15]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation